Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Konsumen Honda Beat pada PT. Sinar Sentosa Primatama Kota Jambi (Studi Kasus pada Mahasiswa/i Program Studi Manajemen Fakultas Ekonomi Universitas Batanghari Jambi) - Sofyan Wahyudi (Science of Management and Students Research Journal (SMS), 2020)
This research aims to find out Whether Product Quality Factors, Service Quality, Emotional Factors, Cost and Ease Affect Honda Beat Consumer Satisfaction, Analyzing Which Factors - Factors That Most Affect Honda Beat Consumer Satisfaction. This research is a descriptive study and multiple regression analysis. The methods of data collection used are observations, questionnaires, interviews, and documentation. The determination coefficient is useful for looking at the amount of influence of bound variables. PT. Sinar Sentosa Primatama Jambi is one of the automotive companies in Jambi, PT. Sinar Sentosa Primatama is a trading company managed by a large family of Attan clan. In 1971, PT. Sinar Sentosa Primatama achieved satisfactory results and got and got an offer from PT. Astra Honda Sales Operation to become a Honda Motorcycle Main Dealer in Jambi Province. Calculation SPSS Y = 1,229 + 0,065 X1 + 0,132 X2 - 0,041 X3 + 0,522 X4 + e. The equation will be seen that the Emotion Factor (X3) has a negative relationship to honda beat consumer satisfaction. From the result of the SPSS value, r (coefficient) obtained a figure of 0,715 states that the free variable capable of explaining a bound variable is 71,5% and the remaining 28,5% is explained by other factors not included in the research model. Based on a score of 353,75 means product quality is on the criteria of satisfied. Based on a score of 322,7 means the Quality of Service is on the criteria quite satisfied. Based on an average score of 343,75 means the Emotion Factor is on the satisfied criteria. Based on a score of 346,5 means Cost and Convenience are on the criteria of satisfied.